Comprehensive analysis and design of furnace oil-based power station using ETAP - Raheel Muzzammel; Rabia Arshad (Institute of Advanced Engineering and Science, 2022)
High standards of living are linked with the availability of energy. Therefore, there is always a requirement to modify existing power generating systems or to add new systems to fulfill the increasing demands of energy. It is becoming a core issue in the South Asian region so that at least current standards of living could be maintained by controlling growing energy rates and shortening the availability of conventional sources. Furnace oil is a residue obtained in the process of distillation of crude oil in the petroleum industry. This furnace oil is applicable for power generation plants allied with the petroleum industry so that residue of oil refineries could be utilized. In this research, a furnace oil-based power plant is designed in electrical transient and analysis program (ETAP) software. Moreover, steady-state and transient analysis of the proposed design of the power plant are conducted to increase practical viability of model. Load flow is analyzed to depict the performance of the power plant model under load conditions. This model is further tested under the motor starting event to analyze the current drawn by the motor. This event helps to determine the permissible values of protective equipment installed in power plants. In the last, economic dispatch analysis is conducted to find the relative minima of generation cost of furnace oil-based power plant with respect to coal and hydel generation